Pemanfaatan probiotik dalam cookies labu kuning sebagai strategi pengembangan produk biskuit fungsional - Monica Ageng Wardani; Lusiawati Dewi (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
Background: Pumpkin (Curcubita moschata Durch) is a type of vegetable that can be easily damaged like cracked or scratched as the harvesting or post-harvesting time. Those imperfect pumpkins will be rotten in a short time so that they cannot be sold in the market. Therefore, they need to be processed into a durable functional food in the form of cookie; the pumpkin is as the main ingredient for the dough and Lactobacillus sp, the probiotics bacteria is added into it. Research purposes: The aim is to find out the exact concentration of the coating materials’ combination and find out the viability of probiotics which is encapsulated in the maltosedextrin. Method: The coating materials’ combination is examined through encapsulation process using 10 % skimmed milk with three different precentage of maltodextrin i.e. 10%, 15% and 20%. The viability test was carried out using the spread plate method and then analyzed using the Colony Forming Unit and Viability (%) calculation method. Results and Discussion: The coating materials’ combination at concentration of 10% skimmed milk + 10%, 15% and 20% maltodextrin produce 84%, 90% and 98% cells’ viability. This shows that the use of those combinations can maintain the viability of the bacteria from the heat during the baking process at 180°C for 13 minutes. Conclusion: The microencapsulation of Lactobacillus achidopilus and Bifidobacterium logum with 10% skimmed milk + 20% maltodextrin resulted in the best viability as much as 98% viability cells. The higher the maltodextrin amount, the greater the bacterial’s viability is.